Analisis Kinerja Keuangan Perbankan Syariah dan Konvensional Sebelum dan Sesudah Covid-19 di Indonesia Periode 2016-2023 - Muhammad, Auzia Hilmy (Al-Musthofa: Journal of Sharia Economics, 2024)
Abstract: The impact of Covid-19 includes slowing financing growth and increasing financing problems because many people have lost their source of income. This research aims to find out whether there are differences in the financial performance of Sharia and conventional banks between before and after the Covid-19 pandemic. The samples taken were some Sharia and conventional banks that publish annual financial report data from 2016 to 2023. The number of samples in this research was 5 conventional banks and 5 sharia banks. Testing methods and data analysis using Eviews. The results of this research show that a comparison of financial performance between conventional and sharia banking before the COVID-19 pandemic shows that there is no significant difference in financial performance based on CAR, NPL/NPF and ROA ratios in sharia banking. However, there are significant differences in financial performance based on BOPO and FDR/LDR ratios in Islamic banking. The financial performance of conventional banks showed a decline after the COVID-19 pandemic based on the CAR, NPL/NPF, ROA and BOPO ratios, while the FDR/LDR ratio showed an increase. Meanwhile, the financial performance of conventional banks is worse compared to sharia banks after the Covid-19 pandemic based on CAR, NPL/NPF and BOPO, but better based on ROA and FDR/LDR.